Concerted Action of AMPK and Sirtuin-1 Induces Mitochondrial Fragmentation Upon Inhibition of Ca2+ Transfer to Mitochondria - Lovy, Alenka; Ahumada-Castro, Ulises; Bustos, Galdo; Farias, Paula; Gonzalez-Billault, Christian; Molgó, Jordi; Cardenas, Cesar (Frontiers in Cell and Developmental Biology, 2020)
Mitochondria are highly dynamic organelles constantly undergoing fusion and fission. Ca2+ regulates many aspects of mitochondrial physiology by modulating the activity of several mitochondrial proteins. We previously showed that inhibition of constitutive IP3R-mediated Ca2+ transfer to the mitochondria leads to a metabolic cellular stress and eventually cell death. Here, we show that the decline of mitochondrial function generated by a lack of Ca2+ transfer induces a DRP-1 independent mitochondrial fragmentation that at an early time is mediated by an increase in the NAD+/NADH ratio and activation of SIRT1. Subsequently, AMPK predominates and drives the fragmentation. SIRT1 activation leads to the deacetylation of cortactin, favoring actin polymerization and mitochondrial fragmentation. Knockdown of cortactin or inhibition of actin polymerization prevents fragmentation. These data reveal SIRT1 as a new player in the regulation of mitochondrial fragmentation induced by metabolic/bioenergetic stress through regulating the actin cytoskeleton.